2023
DOI: 10.1002/bab.2449
|View full text |Cite
|
Sign up to set email alerts
|

Ornamental cabbage (Brassica oleracea var. acephala) responses to phytase enzyme purified from Lactobacillus coryniformis application

Abstract: In order to increase the quality and yield of ornamental plants, especially potted ornamental plants, it is necessary to enrich the physical properties of the growing medium and to ensure the continuity of the growing medium. In order to achieve this, organic substances that create a serious cost in ornamental plant cultivation are added to the growing medium. This study was planned to assess the role of inoculation of different levels in the seeds and soaking times of purified phytase, on the plant growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Dikbaş et al [8] determined the phytase activity of L. brevis isolated from kashar cheese as 212.97 U/mL. Dikbaş et al [15] reported the specific activity of phytase enzyme purified and isolated from L. coryniformis as 188.31 (EU mg -1 protein).The data obtained in our study are consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Dikbaş et al [8] determined the phytase activity of L. brevis isolated from kashar cheese as 212.97 U/mL. Dikbaş et al [15] reported the specific activity of phytase enzyme purified and isolated from L. coryniformis as 188.31 (EU mg -1 protein).The data obtained in our study are consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Phytase, one of the industrial enzymes, plays an important role in the field of biotechnology due to its worldwide adoption and being the subject of various studies [9]. Phytases exhibit exceptional versatility in a variety of fields, including human dietary enrichment, animal feed development and industrial processes, driving interest in the discovery of new microorganisms capable of producing phytases [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the ability of the strain to produce phytase enzyme was determined, and the strain exhibited an enzyme activity of 244 U/mL. Similar to the results obtained, there are many studies on LAB phytase production (Demir et al, 2018;Dikbaş, Parlakova Karagöz, et al, 2023;Dikbaş, Uçar, & Alım, 2023;Karagöz et al, 2021).…”
Section: Re Sult and Discussionsupporting
confidence: 63%